Pemanfaatan Teknologi dalam Layanan Cyber Konseling: Sobat Sambat PILAR PKBI Jawa Tengah - Hilyatul Auliya; Dwi Rizqi Raridatusaidah; Anjani Pramesti; Hartatik Hartatik; Muhammad Nur Syafii; Muhammad Nur Hasan; Namira Choirani Fajri (Jurnal Konseling dan Psikologi Indonesia, 2026)
The development of digital technology has brought significant changes to counseling services, particularly in improving access to reproductive health for adolescents. This study aims to analyze the effectiveness and challenges of the digital counseling service Sobat Sambat Pro developed by PILAR PKBI Java as an innovation in youth-friendly services. The method used is a literature review with a descriptive qualitative approach, trough an anlysis of various scientifict sources related to online counseling and adolescent reproductive health. The results of the study show that this service utilizes digital technology and peer counseling approaches to increase adolescents’ knowladge and positive attitudes toward reproductive health. The application of the cyber counseling model enables flexible, inclusive service that maintain user privacy, which is an important aspect in building clien trust. The web-basses system whith the waterfall method also stregthens the effectiveness and security of the service. This research contributes to expanding understanding of technologi integration in professional counseling services and serves as a foundation for developing innovative studies in the field of adolescent reproductive health in the digital era.